ANALYSIS OF MESHING CHARACTERISTICS OF PIN-CYCLOID TRANSMISSION OF RV REDUCER - DU XueSong; YU ZiQiang; ZHU CaiChao; DENG ShiWei; HUANG YuCheng (Jixie qiangdu)
On the basis of analyzing the transmission principle and structure characteristics of the RV reducer,from the point of view of the system,considering the coupling deformation of the two stage transmission system of the RV reducer,the structure of the cycloidal gear spoke and the bearing stiffness,the analysis model of the meshing characteristic of the RV reducer is established. The meshing characteristics of the pin-cycloidal gear transmission of the RV reducer are simulated and analyzed,and the influences of the thickness of the cycloidal gear,the amount of modification and the load on the meshing characteristics are discussed in detail. At the same time,the torsional stiffness of the RV reducer is analyzed according to the analysis model established. Finally,the test of the pressure stress of the tooth root of pin wheel housing of the RV reducer and the test of the torsional stiffness are carried out. The correctness of the simulation analysis is verified.